Bullock and the Aftermath - Sturmthal, Adolf (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This study presents the main recommendations of Lord Bullock's Committee of Inquiry on Industrial Democracy in Great Britain.